Constraints in Adapting the Climate change in Konkan region of Maharashtra - Shelar, Rohit; Singh, A. K.; Maji, Saikat (Indian Journal of Extension Education, 2021)
Changing climate is a serious environmental issue affecting agricultural production all over the world. India is also facing the problem of increased mean temperature and irregularity of rainfall, and the Konkan region of Maharashtra is also not escaped from this issue. The study was designed and conducted in the northern part of the Konkan region to understand the constraints experienced by the farmers while adapting the climate change. The study was carried in four villages of Palghar district with 245 respondents selected by proportionate random sampling method. Major constraints were expressed by the farmers while adapting the changing climate were, lack of credence on current weather forecasting system, poor accurate weather forecast information, irregular & low voltage capacity power supply and seven others.Â